Defibrotide for the treatment of hepatic veno-occlusive disease in children after hematopoietic stem cell transplantation. Issue 3 (June 2012) - Corbacioglu, Selim; Kernan, Nancy; Lehmann, Leslie; Brochstein, Joel; Revta, Carolyn; Grupp, Stephan; Martin, Paul; Richardson, Paul G
Hepatic veno-occlusive disease (VOD) is a serious complication of stem cell transplantation in children. VOD is characterized by rapid weight gain, hepatomegaly, hyperbilirubinemia and ascites. The pathogenesis of VOD is thought to involve chemotherapy and radiation-induced damage to the sinusoidal endothelium, resulting in endothelial injury, microthrombosis, subendothelial damage and cytokine activation. These processes lead to concomitant progressive hepatocellular dysfunction and subsequent fluid retention and renal impairment. Severe VOD is typically associated with multiorgan failure and high mortality. A number of possible strategies for the prevention and/or treatment of VOD in children have been investigated. The most promising agent to date is defibrotide, a novel polydeoxyribonucleotide with fibrinolytic properties but no major bleeding risk. Numerous studies, including Phase II/III trials, have shown clinical benefit in pediatric patients with the use of defibrotide treatment and prophylaxis. This review discusses VOD in children and focuses on therapeutic options, including defibrotide, in this patient population.